Experimental studies on resistance characteristics of high concentration red mud in pipeline transport - 王星 瞿圆媛 胡伟伟 陈洁 赵学义 吴淼 (Journal of coal science & engineering, China, 2008)
Red mud will flow in paste form under high pressure during pipeline transport. It belongs to a two-phase flow of materials with high viscosity and a high concentration of non-sedimentation, homogeneous solid-liquids. In pipeline transport, its resistance char- acteristics will be influenced by such factors as grain size, velocity, concentration, density, grain composition and pipe diameter etc.. With the independently developed small-sized tube-type pressure resistance test facility, studied the resistance characteristics of red mud concerning the three influencing factors, paste concentration, velocity and pipe diameter, which attract the most attention in projects. The fine grain size of the red mud is d50= 13.02 μm. According to the experimental results, the pressure loss in transport will increase along with the increase of velocity and will fall along with the increase of pipe diameter. A 1% difference in paste concentration will result in a 50%-100% difference in pipeline resistance loss. These experimental data is hoped to be direct guidance to the design of high concentration and viscous material pipeline transport system.